(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
The research objective of this article is in the theoretical articulation on how the graphic designer can use his technical and artistic skills in favor of social causes and reflections. For this, critical illustration was adopted as an object of study. Initially the theoretical discussions were oriented to the concepts that contribute, exemplify and justify how the criticism can be made and directed to the current contemporary society. Subsequently, four illustrators from different countries were chosen so that it was possible to demonstrate how their work corroborates the understanding of how graphic design can not only be a professional activity that contributes to a company’s marketing objectives, but can also be an instrument that instigates the questioning and social change through the construction of a critical look.